The Distribution of the Agentive Nominalizer of the Suffixes {-er} and {-an} - Karlina Denistia; Francis Borgias Alip (Journal of Language and Literature, 2014)
This study focuses on the suffixes {er} and {-an} because these suffixes are the most commonly used suffixes in daily life and thus really productive. There are three problems formulated for this topic: (1) What are the characteristics of stems receiving suffixes {er} and {-an}? (2) What meanings are introduced by suffixes {er} and {an}? (3) What are the distributions of the allomorphs of suffixes {er} and {-an}? The data of this study are morphemes and affixes. Hornbys Oxford Advanced Learners Dictionary (year of 2000) is used. Finally, the present researcher found that the suffixes {er} and {an} are attached to certain verbs, adjectives, and nouns. The suffix {-an} are not attached to verbs. The suffix {-er} is mostly attached to transitive verbs to create three possibilities of meaning. There is only one meaning of the suffix {er} when it is attached to an adjective, and eight meanings of the suffix {er} when it is attached to certain nouns. For suffix {-an}, there are three meanings when it is attached to adjectives and five meanings when it is attached to nouns. There are two meanings of the suffix {-an} when it is attached to nouns. The allomorph of the suffix {-er} are or, -eer /??r/, and ier /??r/, while the allomorphs of the suffix {-an} are ian /?n/, -ian /??n/, and ean /??n/. Keywords: morpheme, derivational suffixes, an agentive nominalization, stem, allomorph